2005
DOI: 10.1007/s00421-004-1287-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between maximal power in the power-endurance relationship and maximal instantaneous power

Abstract: The purpose of this study was to analyze the relevance of introducing the maximal power (P(m)) into a critical-power model. The aims were to compare the P(m) with the instantaneous maximal power (P(max)) and to determine how the P(m) affected other model parameters: the critical power ( P(c)) and a constant amount of work performed over P(c)(W'). Twelve subjects [22.9 (1.6) years, 179 (7) cm, 74.1 (8.9) kg, 49.4 (3.6) ml/min/kg] completed one 15 W/min ramp test to assess their ventilatory threshold (VT), five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
12

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 25 publications
(53 reference statements)
1
10
0
12
Order By: Relevance
“…In this case, P c was found to be correlated with various estimates of the ventilatory and lactate thresholds obtained using a single incremental exercise or a series of long duration exercises (Lechevalier et al 1989;Sid-Ali et al 1991;McLellan and Cheung 1992;Pringle and Jones 2002;Moritani et al 1981;Bulbulian et al 1986;Gaesser et al 1995;Smith et al 1999;Chatagnon et al 2005). However, some authors reported that P c was higher than the power at maximal lactate steady state (Pringle and Jones 2002;Dekerle et al 2003).…”
Section: Introductionmentioning
confidence: 69%
“…In this case, P c was found to be correlated with various estimates of the ventilatory and lactate thresholds obtained using a single incremental exercise or a series of long duration exercises (Lechevalier et al 1989;Sid-Ali et al 1991;McLellan and Cheung 1992;Pringle and Jones 2002;Moritani et al 1981;Bulbulian et al 1986;Gaesser et al 1995;Smith et al 1999;Chatagnon et al 2005). However, some authors reported that P c was higher than the power at maximal lactate steady state (Pringle and Jones 2002;Dekerle et al 2003).…”
Section: Introductionmentioning
confidence: 69%
“…The power chosen for the tests could also explain the conflicting findings concerning the interpretation of W 0 . When using power lower than maximal aerobic power to establish the power-time to exhaustion relationship, W 0 was almost twice the maximal oxygen deficit, although a significant correlation was observed between them (Chatagnon et al 2005). This led us to propose a segmented model with a break point (P t ) corresponding to the lowest power required to achieve the maximal aerobic power Chatagnon and Busso 2006), whereas P c remained the power asymptote for time tending towards infinity.…”
Section: Introductionmentioning
confidence: 99%
“…Uma possível explicação para o fenômeno seria que o esforço percebido nas intensidades severas (9) seria regulado pela velocidade de utilização da capacidade de trabalho anaeróbio (CTA). Esse segundo parâmetro do modelo é representativo da capacidade de transferência energética a partir dos estoques de fosfagênios e da glicólise anaeróbia (7,17,18) . Assim, o esforço percebido em intensidades acima da VC seria uma conseqüência dos distúrbios periféricos associados à depleção de fosfagênios e acidose metabólica, concomitante à mobilização crescente da atividade neuromotora eferente (6) .…”
Section: Perceived Exertion During Swimming Interval Training At Inteunclassified
“…Quando o indivíduo realiza exercí-cios acima da VC, há a utilização da CTA para complementar a demanda necessária do exercício que não consegue ser suprida pelo sistema aeróbio, e quando ocorre o esgotamento dessa reserva, o indiví-duo entra em exaustão. Alguns estudos têm demonstrado que CTA está relacionada ao máximo déficit acumulado de oxigênio (7,14) . Esses pressupostos confirmam parte das previsões inicialmente delineadas para este estudo baseadas em nossos estudos recentes (19,20) , em que observamos que a taxa de aumento do esforço percebido, em cargas severas de trabalho (9) , era proporcional à intensidade do exercício.…”
Section: Tratamento Estatísticounclassified